Proceedings of the 2021 ACM Symposium on Principles of Distributed Computing 2021
DOI: 10.1145/3465084.3467934
|View full text |Cite
|
Sign up to set email alerts
|

Locally Checkable Problems in Rooted Trees

Abstract: Consider any locally checkable labeling problem Π in rooted regular trees: there is a finite set of labels Σ, and for each label ∈ Σ we specify what are permitted label combinations of the children for an internal node of label (the leaf nodes are unconstrained). This formalism is expressive enough to capture many classic problems studied in distributed computing, including vertex coloring, edge coloring, and maximal independent set.We show that the distributed computational complexity of any such problem Π fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…A recent work [8] gave a complete classification of possible complexities of LCLs on rooted regular trees, showing that each LCL on such trees has a complexity of Op1q, Θplog ˚nq, Θplog nq, or Θpn 1{k q for some positive integer k (and all of these complexity classes are nonempty). Moreover, the complexity of each LCL is independent of whether randomization is allowed and whether the LOCAL or the CONGEST model 3 is considered.…”
Section: Main Contribution: Finishing the Classification Of Lcls On T...mentioning
confidence: 99%
See 3 more Smart Citations
“…A recent work [8] gave a complete classification of possible complexities of LCLs on rooted regular trees, showing that each LCL on such trees has a complexity of Op1q, Θplog ˚nq, Θplog nq, or Θpn 1{k q for some positive integer k (and all of these complexity classes are nonempty). Moreover, the complexity of each LCL is independent of whether randomization is allowed and whether the LOCAL or the CONGEST model 3 is considered.…”
Section: Main Contribution: Finishing the Classification Of Lcls On T...mentioning
confidence: 99%
“…For instance, the asymptotic complexity of problems from a natural subclass of LCLs, called binary labeling problems can be decided efficiently [4]. Moreover, in their work providing the complexity clas-sification of LCLs on regular rooted trees [8], the authors showed that it is decidable into which of the four complexity classes Op1q, Oplog ˚nq, Θplog nq, and n Θp1q a given LCL without inputs falls. The decidability is achieved by defining so-called "certificates" for Oplog nq-round, Oplog ˚nq-round, and constant-round solvability-for each T from tOplog nq, Oplog ˚nq, Op1qu, an LCL problem is T -round solvable if and only if there exists a certificate for T -round solvability for the given LCL problem, and the existence of such a certificate is decidable.…”
Section: Decidabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…They considered bounded-degree graphs and showed that there exist non-trivial problems, such as the weak 2-coloring that can be solved in constant time. Today, LCL problems are well classified with respect to their computational complexity for the special cases of paths [3,4,11,16,35], grids [11], directed and undirected trees [4,5,7,13,15] as well as general graphs [11,35], with only a few unknown gaps [5]. In an attempt to overcome issues with symmetry-breaking in the LOCAL model, the SLOCAL [23] model has been introduced.…”
Section: Related Workmentioning
confidence: 99%